A study of 82 patients of non-traumatic terminal ileal perforation in Al-Kindy teaching hospital. - Abdullah, Muhamad S.; Rassam, Raid E.; Almarzooq, Tawfiq J. (Journal of the Faculty of Medicine Baghdad, 2011)
Background typhoid fever is the commonest cause of non traumatic terminal ileal perforation in our study with a grave postoperative morbidity & mortality depending upon preoperative time delay &/or type of surgical intervention practiced. Objective to evaluate the frequency of non traumatic causes of terminal ileal perforation, their presentations,perforation-operation interval effect on complications, as well as different modalities of treatment and their complications.Methods the study is a prospective study of 82 patients with perforation of terminal ileum diagnosed by explorative laparatomy in Al Kindy teaching hospital ,Baghdad, Iraq from April 2008- December 2010, all of the patients were examined clinically & investigated by plain x-ray of abdomen, ultrasound, complete blood picture, laparatomy was done for them after resuscitation and intravenous antibiotic, tissue biopsy was taken for paraffin section histopathological examination, and patients were followed for complications.Results: the study of 82 patients revealed that their mean age 42 years (±14) ranging from16-75 years, with male to female ratio is 2, 28:1. The main cause of perforation is enteric fever 59 (71.95%) of patient, non specific inflammation 17(20.74%), Chronic granulomatous lesion 5(6.1%). The main presenting symptom in all patients was severe abdominal pain associated with fever, and abdominal distention in variable degree.The operative finding was single perforation in 61patients(74%) , two perforations in 8 patients(10%) and multiple in 13 patients(16%). The simple closure was done in 50 patients(60%), and other treated by resection and end to end anastomosis , Loop ileostomy,Resection and ileotransverse anastomosis, and follow up of patients revealed that 7(8%) died postoperatively , 3 patients(3.6%) developed wound dehiscence,6 patients(7%) developed enterocutanous fistula ,10 patients (12.1%) developed wound infection and 6 patients (7.3%) developed residual collection. Conclusion non-traumatic perforation of terminal ileum is not uncommon and the most common cause is typhoid fever, and carries high mortality and morbidity rates specially in delayed presentation & diagnosis group of patients.